Legal Political Perspective Wage System to Realize Social Justice - Endeh Suhartini (Faculty of Law, Universitas Sebelas Maret, 2020)
Manpower development is based on Pancasila and the 1945 Constitution of the Republic of Indonesia as regulated in the Manpower Act. In its implementation, labor relations aim to improve the welfare of workers and their families and create social justice in work relations that protect the interests of workers and companies for the sustainability of work relations. This research is empirical, descriptive, and explorative in nature. The results of the study show first.